Pengaruh Live Streaming Dan Diskon Flash Sale Terhadap Impluse Buying Pada Pengguna Shopee Di Kota Palopo - Aldi; Kadek Cahaya Krisna; Ferdi Tiranda; Nurjannah; Nurfatimah (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2026)
This study aims to determine and analyze the effect of live streaming and flash sale discounts on impulse buying among Shopee users in Palopo City. This study was quantitative. The data used were primary and secondary data. Data collection was conducted through observation, interviews, and questionnaires. A sample size of 60 was used. Data analysis included descriptive analysis, validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis.The results showed that simultaneously, live streaming and flash sale discounts significantly influenced impulse buying. Partially, live streaming did not significantly influence impulse buying among Shopee users in Palopo City. Meanwhile, flash sale discounts significantly influenced impulse buying among Shopee users in Palopo City.